The abolition of the earnings rule for UK pensioners - Richard Disney; Sarah Tanner (Institute for Fiscal Studies (IFS), 2000)
The US has legislated to abolish its social security earnings test. A priori it is not possible to predict the effect this will have on work incentives. Using data from the Family Expenditure Survey we show that the abolition of the earnings rule in the UK increased the number of hours worked by men. The lack of any evidence of a reduction in hours may be a consequence of those who previously earned more than the earnings threshold deferring pension receipt at an actuarially favourable rate. This is consistent with there being little evidence of a significant change in the number of deferrals after the earnings rule was abolished.
Keywords: 330; Altersvorsorge; Lohn; Arbeitszeit; Arbeitsangebot; Großbritannien